Access to Justice: The Readability of Legal Services Corporation Legal Aid Internet Services. Issue 2 (4th March 2017) - Dyson, Dana D.; Schellenberg, Kathryn
ABSTRACT: Readability of existing legal-aid websites exceeds Federal standards and the reading ability of most Americans. Legal Services Corporation supported the development of online legal content to mitigate access barriers to civil legal-aid. A t-test analysis, using Flesch-Kincaid readability analyses of 407 text passages in LSC-sponsored websites, showed that websites that claim to follow federal readability standards are easier to read than websites that do not make this claim. The websites are still beyond the comprehension of many poor Americans with limited education and literacy skills. In general, these findings underscore a need to develop appropriate readability levels in legal aid websites to improve access for vulnerable populations.